2016
DOI: 10.1007/s10067-016-3271-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between femoral cartilage thickness and muscle strength in knee osteoarthritis

Abstract: To explore whether femoral cartilage thickness is related (and changes) with muscle strength in subjects with knee osteoarthritis (OA). Forty patients (27 F, 13 M) with knee OA-who were under quadriceps muscle strengthening program-were enrolled in the study. Isokinetic/isometric knee muscle strength measurements (at 30-60° angles and 60-180° velocity) were performed at baseline, end of the muscle strengthening program, and third month control visit using a biodex dynamometer. Femoral cartilage thicknesses (at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…They also found a significant decrease in the VAS scores; however, they failed to show a significant change in the WOMAC subscores with isokinetic exercises. [9] One of the limitations of this study was that the patients performed only a single day of isokinetic exercise program with 30°/sec, 60°/sec, 90°/sec and 180°/sec angular velocities. Then, the patients moved on a home-based exercise program.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…They also found a significant decrease in the VAS scores; however, they failed to show a significant change in the WOMAC subscores with isokinetic exercises. [9] One of the limitations of this study was that the patients performed only a single day of isokinetic exercise program with 30°/sec, 60°/sec, 90°/sec and 180°/sec angular velocities. Then, the patients moved on a home-based exercise program.…”
Section: Discussionmentioning
confidence: 96%
“…In their study, Tuna et al [9] investigated whether femoral cartilage thickness changed with muscle strengthening exercises. The authors found a positive correlation between the femoral cartilage thickness and muscle strength at three months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between knee pain while rising from a chair or while stepping and K/L grade was considered. Previous studies have reported that the thickness of the femoral articular cartilage correlates with the strength of the quadriceps [40]. Moreover, according to previous studies, in patients with osteoarthritis of the knee, the lower the muscle strength of the quadriceps muscle, the worse the condition of the knee joint on radiographic evaluation [41].…”
Section: Discussionmentioning
confidence: 97%
“…58 A single session of quadriceps strengthening can lead to a significant decrease in intra-articular levels of COMP in joint synovial fluid while observing no appreciable change in other biomarkers of inflammation and cartilage turnover, suggesting a biological benefit to cartilage health. 81 Other studies evaluating quadriceps strengthening more longitudinally over the course of 3 months have also demonstrated improved femoral cartilage thickness 82 and greater molecular weight of hyaluronic acid and viscosity of joint synovial fluid (both indicators of joint health). Additionally, a concurrent decrease in levels of chondroitin sulfate, a major GAG and primary component of articular cartilage, would suggest less cartilage tissue turnover.…”
Section: Resistance Exercisementioning
confidence: 99%